Drug-Induced Extrapyramidal Symptoms at the Pediatric Emergency Department. Issue 10 (October 2020) - Chang, Ming-Yu; Lin, Kuang-Lin; Wang, Huei-Shong; Wu, Chang-Teng
Abstract : Objectives: Extrapyramidal symptoms (EPS) induced by pharmacologic agents can cause patient discomfort and lead to emergency department visits. Analyzing these cases at a pediatric emergency department may help to elucidate the characteristic features of extrapyramidal syndrome in children. Methods: This retrospective study was conducted at Chang Gung Memorial Hospital in Taiwan. Pediatric patients with drug-induced extrapyramidal syndrome seeking treatment at our emergency department from January 2001 to December 2010 were enrolled. The patients' clinical features, drug history, demographic data, and treatment data were collected and analyzed. Results: One hundred nineteen patients (61 females, 58 males) were enrolled. Ninety-six patients could provide their drug history; all of whom took dopamine antagonists and 90% of whom took dopamine antagonists as antiemetic agents, with only 9 patients taking them for antipsychotic purposes. Metoclopramide syrup overdose was the main cause of extrapyramidal syndrome in patients under 2 years old. The average emergency room stay of the patients who could provide their drug history was shorter than that of those who could not. Conclusions: It is not uncommon for patients with drug-induced EPS to present to a pediatric emergency room owing to the use of dopamine antagonists as antiemetic agents. Clinical symptoms with a clear drug history are helpful for the diagnosis and management. Emphasizing the correct usage of liquid medications will reduce the risk of EPS.